1991
DOI: 10.1213/00000539-199103000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Postoperative Regional Analgesia by Nerve Sheath Block for Amputation Surgery-A Pilot Study

Abstract: A pilot study of continuous postoperative regional analgesia by nerve sheath block for lower limb amputation is presented. At the time of exposure of sciatic or posterior tibial nerve trunks during above- or below-knee amputations in 11 patients with ASA physical status III or IV, a catheter was introduced directly into the transected nerve sheath for continuous infusion of 0.25% bupivacaine at a rate of 10 mL/h for 72 h. Effective amputation stump analgesia was obtained, significantly reducing the need for on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
79
0
3

Year Published

1996
1996
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(83 citation statements)
references
References 0 publications
1
79
0
3
Order By: Relevance
“…Those blocks provided short-term pain relief and the patients used less morphine for 2-3 days. Despite these early benefits, the two studies' intervention and control groups did not differ in the amount or severity of pain they felt after the third day (16).…”
Section: Discussionmentioning
confidence: 89%
“…Those blocks provided short-term pain relief and the patients used less morphine for 2-3 days. Despite these early benefits, the two studies' intervention and control groups did not differ in the amount or severity of pain they felt after the third day (16).…”
Section: Discussionmentioning
confidence: 89%
“…But it is possible that the prolonged block administered intraoperatively soon after the peripheral trauma of amputation and continued into the postoperative period may modify and reduce the hyper excitability response of the spinal cord. 10 12 Lambert et al conducted a study of 30 patients scheduled for lower limb amputations; 14 patients received epidural bupivacaine for 24 hours before and during surgery and 3 days postoperatively, and 16 patients had an intraoperatively placed perineural catheter for intra and postoperative administration of bupivacaine. They concluded that the perioperative epidural block is not superior to perineural catheter in preventing phantom pain.…”
Section: Discussionmentioning
confidence: 99%
“…10 and that of the below knee stump from the common peroneal nerve. This could be because of the stump being bathed by the large volume of local anaesthetic being infused.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is certainly an excellent help in surmounting the difficulties of the first few days. Spinal anaesthesia or injection of the sciatic or femoral nerve trunk can be used, leaving a fine catheter in place for a few days to allow repeated injections [5,8].…”
Section: Perioperative Carementioning
confidence: 99%